Simplified modelling of photonic-crystal-confined vertical-cavity surface-emitting diode lasers - Nakwaski, Włodzimierz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In standard GaAs-based oxide-confined vertical-cavity surface-emitting diode lasers (VCSELs), their transverse single-fundamental-mode operation is limited to relatively low outputs. It is a direct consequence of small radial sizes of their active regions and strong real waveguiding effects induced by their oxide apertures. Photonic crystals applied in VCSEL designing in a way shown in the present paper enable a subtle waveguiding modification leading to a considerable increase in an output of the VCSEL single-mode operation. Unfortunately, the structure of a photonic crystal damages inside a VCSEL volume its axial symmetry, which makes rigorous simulation of its operation much more difficult. In the present paper, a simplified approach to physical (optical, electrical and thermal) phenomena taking place within VCSEL volumes equipped with photonic crystals is presented. Designing guidelines to obtain single-mode-operating photonic-crystal-confined VCSELs have been proposed. Various possible distributed-Bragg-reflector (DBR) output mirrors designed for various wavelengths have been analysed. From among them, GaN-based DBRs have been found to enable higher single-mode VCSEL outputs, especially for longer wavelengths.
Optica Applicata, Vol. 35, 2005, nr 3, s. 579-589
Keywords: optyka; photonic crystals; vertical-cavity surface-emitting diode lasers (VCSELs); photonic-crystal-confined VCSELs; simplified VCSEL modelling